Innovative Solutions for Portable Wind Turbines, Used on Ships. (2015) - Ionescu, Raluca Dora; Szava, Ioan; Vlase, Sorin; Ivanoiu, Mircea; Munteanu, Renata
Abstract: The paper aims to analyse the wind turbine solutions implemented on ships. Also a thorough study of the blade design solutions for small power Vertical Axis Wind Turbines (VAWTs) has been conducted, with their advantages and disadvantages, such as in the end to be able to present the best solution for a new design that has as objective the minimisation of loads and vibrations. First are presented all the solutions, next are discussed several research results for each solution and, in the end, a combination of solutions is chosen for the new small power VAWT.